Granting Exclusive Right to Provide the Base Transceiver Station Tower in a Regency Reviewed from The Competition Law - Tessana Pridia Paramitha; Sinar Aju Wulandari (Transpublika Publisher, 2025)
The Badung Regency Government in 2007 made an agreement with a company which gave exclusive rights to that company as the only business actor permitted to build and manage Base Transceiver Station (BTS) towers in Badung Regency. This agreement prohibited the Badung Government from granting tower permits to other companies. The action taken by the Badung Government created barriers for other companies attempting to enter the BTS tower industry in Badung Regency. Therefore, the purpose of this research is to analyze barriers to entry in the BTS tower leasing market in Badung Regency. This research will analyze monopolistic practices in BTS tower leasing in Badung Regency based on the provisions regulated in Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition. This research uses normative legal research methods with statute approach, conceptual approach, and case approach. The results of this study indicate that the existence of exclusive rights to provide BTS towers in Badung Regency raised barriers to entry into the BTS tower leasing business. These entry barriers caused the company that was given exclusive rights to have a monopoly position in the leasing of BTS towers in Badung Regency. This condition has negative impacts on other business actors, consumers, and the Badung community.